Divina Comedia. Dante Alighieri. Edición anotada bilingüe. - Blanco Jiménez, José (Scripta Mediaevalia, 2026)
The article focuses on the bilingual annotated edition in Spanish and Italian of Dante Alighieri's *Divine Comedy*, published by Ediciones Akal in 2021 on the occasion of the VII Centenary of the poet's death. Coordinated by Rossend Arqués and mainly translated by the Dante scholar Raffaele Pinto, this monumental three-volume edition includes an extensive critical apparatus, illustrations of medieval manuscripts and works by renowned artists, as well as 18 thematic essays that facilitate a multifaceted reading of the text. Pinto chose to base the translation on the critical text established by Giorgio Petrocchi, although he incorporates variants and detailed philological explanations, and makes linguistic and onomastic interventions, especially in complex passages such as those of the Malebranche devils, whose names were adapted into Spanish by Juan Varela-Portas de Orduña. The work is valued as a rigorous resource of great bibliographic worth, aimed both at scholars and readers interested in universal culture.